Crusading as an act of vengeance, 1095 - 1216 - Throop, Susanna A. (Routledge, Taylor and Francis Group, 2020)
The meanings of vindicta, ultio, and venjance -- Early years : crusading as vengeance, 1095-1137 -- A growing appeal : crusading as vengeance, 1138-1197 -- Popular or papal? : crusading as vengeance, 1198-1216 -- Zelus : an emotional component of crusading as vengeance